A catalyst-free, efficient green MCR protocol for access to functionalized γ-carbolines in water1. Issue 65 (16th July 2015) - Dagar, Anuradha; Biswas, Soumen; Samanta, Sampak
<x xml:space="preserve">Abstract</x> A catalyst-free green procedure for access to substituted γ-carbolines has been achieved in water with excellent yields via a MCR reaction of 3-formyl indole derivatives, aldehydes with NH4OAc at room temperature under aerobic conditions.